Microbial Interventions in Bioremediation of Heavy Metal Contaminants in Agroecosystem - Pande, Veni; Pandey, Satish Chandra; Sati, Diksha; Bhatt, Pankaj; Samant, Mukesh (Frontiers in Microbiology, 2022)
Soil naturally comprises heavy metals but due to the rapid industrialization and anthropogenic events such as uncontrolled use of agrochemicals their concentration is heightened up to a large extent across the world. Heavy metals are non-biodegradable and persistent in nature thereby disrupting the environment and causing huge health threats to humans. Exploiting microorganisms for the removal of heavy metal is a promising approach to combat these adverse consequences. The microbial remediation is very crucial to prevent the leaching of heavy metal or mobilization into the ecosystem, as well as to make heavy metal extraction simpler. In this scenario, technological breakthroughs in microbes-based heavy metals have pushed bioremediation as a promising alternative to standard approaches. So, to counteract the deleterious effects of these toxic metals, some microorganisms have evolved different mechanisms of detoxification. This review aims to scrutinize the routes that are responsible for the heavy metal(loid)s contamination of agricultural land, provides a vital assessment of microorganism bioremediation capability. We have summarized various processes of heavy metal bioremediation , such as biosorption, bioleaching, biomineralization, biotransformation, and intracellular accumulation, as well as the use of genetically modified microbes and immobilized microbial cells for heavy metal removal.